Loafers Are Not Going to Subsist Upon Public Credulence: Vagrancy and the Law in Calgary, 1900-1914 - Bright, David (Labour / Le Travail, 1995)
Between 1900 and 1904, rapid growth in population and industrial production transformed Calgary. It was also a period in which those arrested and charged with vagrancy appeared before the local police court in increasing numbers. Previous studies have suggested that the prosecution of vagrants amounted to a form of social control. Reflecting the values of the dominant middle class, local authorities sought to suppress or reform anyone who rejected those same values, especially those connected to the importance of work. This article argues that, in Calgary at least, the criminal justice system lacked the intent or means to reform vagrants. Instead, it punished them as an example to the wider working class of the penalty for rejecting the work ethic.
Keywords: Alberta; CALGARY (Alta.); CRIMINAL justice administration; LABOUR/LE Travail (Book); PROSECUTION; SLACKERS; VAGRANCY; VICTIMLESS crimes